PENGARUH PELIMPAHAN WEWENANG DALAM HUBUNGAN PARTISIPASI PENYUSUNAN ANGGARAN DENGAN KINERJA (STUDI PADA UNIT KEGIATAN MAHASISWA FAKULTAS EKONOMI UAD) - Sumaryanto, Sumaryanto (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2013)
Prior research found inconsitency result about relationship between participation budgeting with performance. This research is deigned to find out the effect of decentralization on relation participation budgeting to performance in organization student of Economic Faculty Ahmad Dahlan University.Data were collected by performing laboratory experiment with 2x2 factorial designs. The subjects in this research were 80 Accounting Department students of Ahmad Dahlan University, but four students incomplete to answer my questionnaire. Hypothesis was tested using 2x2 Anova.This research found that performance of student have participation budgeting higher than students havenât participation budgeting on decentralization systems (p-value = 0.018), decentralization influenced relationship between participation budgeting with performance (p-value = 0.026).